2008
DOI: 10.1289/ehp.11167
|View full text |Cite
|
Sign up to set email alerts
|

Bone Resorption and Environmental Exposure to Cadmium in Women: A Population Study

Abstract: BackgroundEnvironmental exposure to cadmium decreases bone density indirectly through hypercalciuria resulting from renal tubular dysfunction.ObjectiveWe sought evidence for a direct osteotoxic effect of cadmium in women.MethodsWe randomly recruited 294 women (mean age, 49.2 years) from a Flemish population with environmental cadmium exposure. We measured 24-hr urinary cadmium and blood cadmium as indexes of lifetime and recent exposure, respectively. We assessed the multivariate-adjusted association of exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
119
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 197 publications
(127 citation statements)
references
References 43 publications
5
119
1
2
Order By: Relevance
“…unlikely to be the proposed link between Cd-induced effects on kidney and bone. (33) Furthermore, the positive association between U-Cd and urinary calcium observed previously (26,29,30) and in this study has been considered a result of Cd-induced tubular damage causing hypercalciuria but may well be a result of Cd-induced increased bone resorption. (29,30) U-Cd also has been shown to be associated with both increased bone resorption and decreased parathyroid hormone concentrations, (6,26) suggesting that the effect on bone was not mediated primarily by Cd-induced tubular damage.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…unlikely to be the proposed link between Cd-induced effects on kidney and bone. (33) Furthermore, the positive association between U-Cd and urinary calcium observed previously (26,29,30) and in this study has been considered a result of Cd-induced tubular damage causing hypercalciuria but may well be a result of Cd-induced increased bone resorption. (29,30) U-Cd also has been shown to be associated with both increased bone resorption and decreased parathyroid hormone concentrations, (6,26) suggesting that the effect on bone was not mediated primarily by Cd-induced tubular damage.…”
Section: Discussionsupporting
confidence: 57%
“…Human data support Cdinduced increased bone resorption rather than an effect on bone formation. (6,29,30) Our results on fracture risk suggest, however, that Cd's effect is only partly mediated via lowered BMD. It can be speculated that Cd exposure also results in specific effects on cortical and trabecular bone or in alterations of biomechanical properties that are not detected by DXA; this is also supported by experimental studies.…”
Section: Discussionmentioning
confidence: 55%
“…(7) Studies among populations from Belgium, (4,8) Sweden, (9)(10)(11) Japan, (12) and China (13,14) showed associations between osteoporosis and low-level environmental cadmium exposure. The generally accepted interpretation has been that cadmiuminduced renal tubular damage (2) decreases the calcium reabsorption in the nephron, resulting in hypercalciuria (2) and low BMD and hence increased fracture risk, (4,11) particularly in postmenopausal women (4,8) or men in the older age group. (11) In keeping with experimental studies, this study supports indirectly the interpretation that cadmium decreases bone density and increases the risk of osteoporosis through a direct osteotoxic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Studies among populations from Belgium (Staessen et al 1999;Schutte et al 2008b), Sweden (Järup et al 1998a;Alfvén et al 2000;Å kesson et al 2006), Japan and China Jin et al 2004;Wang et al 2003) showed associations between osteoporosis and low-level environmental Cd exposure. The generally accepted interpretation has been that Cd-induced renal tubular damage (Staessen et al 1994) decreases the calcium reabsorption in the nephron, resulting in hypercalciuria and decreased bone mineral density, and hence increased fracture risk (Järup et al 1998c;Staessen et al 1994) particularly in postmenopausal women (Schutte et al 2008b;Staessen et al 1999) or men in the older age group . However, a recent study also found a dose-response association between odds of osteoporosis in young men (mean age 45) and urinary Cd .…”
Section: Osteoporosismentioning
confidence: 99%
“…Dose-response relationships were reported on urinary Cd as a continuous variable expressed in lg per g creatinine [OR = 1.15 (95% CI 1.00-1.33)]. Recent data provide more insight into the mechanisms supporting a direct osteotoxic effect of Cd independent of the status of kidney function in that urinary excretion of pyridinium crosslinks from bone collagen is increased (Schutte et al 2008b). The shape of this association was linear with effects observed at low levels ( Table 1).…”
Section: Osteoporosismentioning
confidence: 99%